Gambaran Kualitas Hidup pada Pasien Diabetik Retinopati Berdasarkan Tingkat Keparahan Visus - Novita Dhewi Ikakusumawati; Dewi Magistasari; Novena Adi Yuhara; Tri Murti Andayani; Supanji Supanji; Susi Ari Kristina (Faculty of Pharmacy, Universitas Gadjah Mada)
Diabetic retinopathy (DR) is one of the microvascular complications of diabetes mellitus (DM) which incidence increases with the high prevalence of DM. The presence of these complications will affect quality of life, especially vision-related. The purpose of this study was to determine the quality of life in RD patients assessed using the VFQ-25 and EQ-5D questionnaires, and to determine the of quality of life based on the visual acuity (VA) severity. This study was an observational study in outpatient with diabetic retinopathy during October 2018 – Januari 2019 period, in RSUP dr. Sardjito and RS Mata Dr. YAP, Yogyakarta. The design of this study was cross sectional which observed quality of life and vision. Quality of life was measured by specific for vision instrument (NEI-VFQ-25) and generic instrument (EQ-5D-5L). The number of patients in this study were 100 patients with an average age of 55 years, the most frequent type of RD was 84% proliferative RD. The average quality of life scores in RD patients measured using the VFQ-25 and EQ-5D utility questionnaires were 64.1 ± 16.2 and 0.61 ± 0.24, respectively. Based on VFQ-25, the most affected subscales were driving, dependence, and role difficulties subscale. Meanwhile, domains that have the most problems with the EQ-5D were pain / discomfort and anxiety / depression (78%). The total VFQ-25 score decreased with increasing visual severity, i.e. normal / mild (n = 19) 73.50 ± 15.08; moderate (n = 15) 68.14 ± 15.33; and severe (n = 66) 60.48 ± 15.64. The EQ-5D utility score showed a similar pattern, with scores of 0.66 ± 0.27 (normal / mild); 0.65 ± 0.22 (medium); and 0.59 ± 0.24 (severe); respectively. The higher severity of visual acuity so the quality of life become lower.